KAJIAN EFEKTIVITAS PENGELOLAAN SIMPANG DENGAN UNDERPASS (STUDI KASUS SIMPANG TUGU NGURAH RAI DI PROVINSI BALI) - Putu Alit Suthanaya; Ni Nyoman Rosita (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2017)
One option to overcome traffic jam that has been implemented was by building Bali Mandara toll road. However, the connection between the toll road with the Tugu Ngurah Rai intersection has caused traffic jam and long queue. Therefore, it is required to analyse appropriate traffic management at Tugu Ngurah Rai intersection. This study aims to analyze the existing performance of Tugu Ngurah Rai roundabout and to provide the alternatives control considering both signalized roundabout and separated-grade intersection of partial-type underpass. The analysis is conducted in accordance to the Indonesian Highway Capacity Manual (MKJI, 1997). The study showed the existing performance of Tugu Ngurah Rai roundabout was at the level of service C. In addition, the degree of saturation, average delay and queue probability of the roundabout were 0.652, 10.802 sec/pcu and 6%-25%, respectively. The roundabout is predicted to reach a level of service D in 2019 with the average delay of 26.664 sec/pcu. Installing signalized traffic control at Tugu Ngurah Rai roundabaout is unable to reduce the congestion, therefore, a separated-grade intersection of underpass is such a plausible alternative. An alternative design of underpass on north-south direction in 2019 is found to be better than east-west direction. The underpass on north-south direction will have a degree of saturation, average delay and queue probability of 0,517, 9.7118 sec/pcu and 12% - 21%, respectively. These condition is equal to a level of service B. Furthermore, considering the increase of traffic flow in 2026, the underpass is predicted to experience a level of service D with average delay of 20.773 sec/pcu. Keywords: roundabout, signal, underpass, performance